Designing Transnational Hydroclimatological Observation Networks and Data Sharing Policies in West Africa. (9th July 2019) - Salack, Seyni; Bossa, Aymar; Bliefernicht, Jan; Berger, Sina; Yira, Yacouba; Sanoussi, Kamil A.; Guug, Samuel; Heinzeller, Dominikus; Avocanh, Adolphe S.; Hamadou, Barro; Meda, Symphorien; Diallo, Belko A.; et al.
Surface observations provide ground evidence of climate change to support the scientific guidance paving the way to better adaptation and mitigation actions. The West African Science Service Centre on Climate Change and Adapted Land Use (WASCAL) has designed a multi-stakeholder initiative to rescue the deteriorated near-surface weather, climate and hydrological equipment of West African countries. The main goal for this multi-stakeholder framework was to monitor the climate and collect long term and high-quality records of essential climate variables in support of research, education, capacity building, and climate services provision. Proactive and inclusive partnership initiatives were developed to jointly (re)design and (re)implement near surface observatiories with the national meteorological and hydrological services or agencies (NMHS/As) in West Africa. The co-production scheme used by this framework succeeded in evaluating the existing observations networks, to modernizing sensors and field equipment, and densifying the sites in order to improve the quality of data collection, transmission, archiving, processing and sharing policies. After more than four years of community-of-practice, the existing regional basic hydroclimatic was increased/upgraded by 45% with automatic weather observing systems while fifty automatic water level, ten water quality sensors, three mesoscale research catchments, and several pilot sites to benefit countries' services provision, research infrastructure, education, and capacity building. Country-specific data sharing policies were harmonized and signed to support data services delivery. This practice paper exposes the concepts, outcomes, challenges, lessons learned and the ways forward in setting-up the framework and keeping it on working to leverage the co-production of data & information services for better-informed decision-making in the field of sustainable development in West Africa.